2020
DOI: 10.3389/feduc.2020.572201
|View full text |Cite
|
Sign up to set email alerts
|

The Effort of Caring: The Caregivers’ Perspective of Dual Sensory Impairment

Abstract: Aim: To explore the social experiences of Dual Sensory Impairment (DSI) for older Australian adults from the perspective of their family carers. Background: DSI in older adults is a chronic progressive disability with varying combined degrees of vision and hearing loss. Prevalence increases with age and is particularly high in those > 85 years of age. Older persons with DSI experience a range of functional, social and emotional health issues and are considered a vulnerable group. Family carers fulfill complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Thirty-four records met the final inclusion criteria after the initial search in June 2019. An updated search was conducted in March 2020, resulting in the identification of three new studies, and a further updated search was conducted in August 2021, where two new studies were identified (Dunsmore et al 2020; Koerber et al 2022) giving; 39 records for inclusion in this review.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-four records met the final inclusion criteria after the initial search in June 2019. An updated search was conducted in March 2020, resulting in the identification of three new studies, and a further updated search was conducted in August 2021, where two new studies were identified (Dunsmore et al 2020; Koerber et al 2022) giving; 39 records for inclusion in this review.…”
Section: Resultsmentioning
confidence: 99%
“…Maintain eye contact, add more pauses to your speech pattern, and enunciate 14. Although it is highly recommended to have a caregiver or partner present during therapy sessions, show respect by continuing to speak and direct all conversation to the patient with DSI 31. Finally, advise an individual with a central scotoma, which could block lipreading, to practice an eccentric gaze strategy 14…”
Section: Dual Sensory Impairmentmentioning
confidence: 99%
“…14 Although it is highly recommended to have a caregiver or partner present during therapy sessions, show respect by continuing to speak and direct all conversation to the patient with DSI. 31 Finally, advise an individual with a central scotoma, which could block lipreading, to practice an eccentric gaze strategy. 14 Written communication will not support auditory communication if it cannot be seen.…”
mentioning
confidence: 99%